SPECIES OF THE GENUS GLOMITES AS PLANT MYCOBIONTS IN EARLY DEVONIAN ECOSYSTEMS - Karatygin I.V.; Snigirevskaya N.S.; Demchenko K.N. (My University, 2006)
Members of the genus Glomites played a prominent role as plant mycobionts in the Early Devonian paleoecosystems. Remains of fossil fungi are studied from silicified tissues of the axial organs of several specimens of the Early Devonian Rhynia gwynne-vaughanii Kidston et Lang and Aglaophyton major (Kidston et Lang) Edwards. Among them a symbiont of vesicular-arbuscular endomycorrhiza, the fungus Glomites, is studied. The morphology of its mycelium, vesicles, glomoid spores, and sporocarps is described in detail. The information obtained allows the description of a new species, Glomites sporocarpoides Karatygin, Snigirevskaya, K. Demchenko et Zdebska. This is the third species of this genus and the first species with sporocarps from Devonian deposits. Fungal sporocarps have been found in both dying plant tissues and in dispersed plant remains. Developmental stages of glomoid spores are revealed. G. sporocarpoides is characterized by the presence of both symbiotic and distinct pathogenic features. Similarities and dissimilarities in the formation of ancient and modern endomycorrhizae are discussed. © Pleiades Publishing, Inc. 2006.
Keywords: EARLYDEVONIAN; MYCORRHIZA; RHYNIOPHYTA; Devonian; Paleozoic::Devonian; Палеозой::Девонская